Prediction of weight increase in anorexia nervosa. (December 2013) - Karlsson, Gunilla Paulson; Clinton, David; Nevonen, Lauri
Abstract Background: Anorexia nervosa (AN) is a serious psychiatric disorder with high mortality rates a poor outcome and no empirically supported treatment of choice for adults. Weight increase is essential for recovery from AN why research exploring important contributors is crucial. Aims: The current study examined the importance of motivation to change eating behaviour, treatment expectations and experiences, eating disorder symptomatology, self-image and treatment alliance for predicting weight increase. Methods: Female patients (n = 89) between 18 and 46 years of age with AN were assessed pre-treatment and at 6- and 36-month follow-ups with interviews and self-report questionnaires. At the 6-month follow-up the response rates differed from n = 58 (65%) to 66 (74%), and at the 36-month follow-up the response rates differed from n = 71 (80%) to 82 (92%). Results: At treatment start, expressed motivation to change eating habits, social insecurity and self-neglect were predictors of weight increase from 0 to 6 months, while duration, the time from onset to entering treatment, body dissatisfaction and interoceptive awareness were predictors of weight increase from 0 to 36 months. Conclusions: In designing treatment for adult patients with AN, it is essential to include multifaceted interventions addressed to patients' motivation to change, social relations, negative self-image and body dissatisfaction in order to achieve weight increase. Early detection and thereby short duration is an additional important factor that contributes to weight increase.